HISTOLOGICAL, HISTOCHEMICAL, AND IMMUNOHISTOCHEMICAL CHARACTERIZATION OF THE EFFERENT DUCTULES OF THE DOVE - Fatma El-Zahraa Ahmed Mustafa; Basim. S. A. Al Sulivany (Science Journal of University of Zakho)
This research examines the structural features of the efferent ductules (EDs) in healthy doves (Spilopelia senegalensis) collected from local hunters in Assiut, Egypt. After slaughter, the efferent ductules were promptly dissected and preserved in Bouin's fluid. Utilizing a combination of histological, histochemical, and immunohistochemical techniques, we explored the architecture of EDs, focusing on the stroma and parenchyma. The lining epithelium was made up of a simple columnar to the pseudostratified columnar epithelium, ciliated, secretory, and basal cells. However, this study is the first to identify telocytes within the peritubular region of the dove’s efferent ductules, highlighting their potential role in tissue communication and regeneration. Additionally, androgen receptor expression was detected in the epithelial cells and spermatozoa within the lumen, suggesting a significant role in the male reproductive system.